EASILY FLAMMABLE SUBSTANCES AND PYROTECHNIC GOODS AS OBJECT OF CRIME ACCORDING TO RUSSIAN CRIMINAL LAW - I. I. Bikeev (Russian Journal of Economics and Law)
In the article on the basis of analysis of published in scientific literature points of view the author makes conclusions and suggestions about conception, indications of easily flammable substances, makes offers on changing existing legislation in the area concerning this problem.